Effect of a synchrotron X‐ray microtomography imaging experiment on the amino acid content of a CM chondrite. (8th January 2016) - Friedrich, Jon M.; Glavin, Daniel P.; Rivers, Mark L.; Dworkin, Jason P.
Abstract: X‐ray microcomputed tomography and synchrotron X‐ray microcomputed tomography (μCT) are becoming popular tools for the reconnaissance imaging of chondrites. However, there are occasional concerns that the use of μCT may be detrimental to organic components of a chondrite. Soluble organic compounds represent 2–10% of the total solvent extractable carbon in CI and CM carbonaceous chondrites and amino acids are among the most abundant compounds in the soluble organic fraction. We irradiated two samples of the Murchison CM2 carbonaceous chondrite under conditions slightly harsher (increased beam exposure time) than those typically used for x‐ray μCT imaging experiments to determine if detectable changes in the amino acid abundance and distribution relative to a nonexposed control sample occurred. After subjecting two meteorite portions to ionizing radiation dosages of 1.1 kiloGray (kGy) and 1.2 kGy with 48.6 and 46.6 keV monochromatic X‐rays, respectively, we analyzed the amino acid content of each sample. Within analytical errors, we found no differences in the amino acid abundances or enantiomeric ratios when comparing the control samples (nonexposed Murchison) and the irradiated samples. We show with calculations that any sample heating due to x‐ray exposure is negligible. We conclude that a monochromatic synchrotron X‐ray μCT experiment at beamline 13‐BM‐D of the Advanced Photon Source, which imparts 1 kGy doses, has no detectable effect on the amino acid content of a carbonaceous chondrite. These results are important for the initial reconnaissance of returned samples from the OSIRIS‐REx and Hayabusa 2 asteroid sample return missions.